Tourism Website as a Market Expansion Strategy in Sumberwringin Village, Bondowoso - Suwignyo Widagdo; Yuniorita Indah Handayani; Riza Bahtiar Sulistyan; Emy Kholifah (Trescode Green Organization, 2025)
The purpose of this activity is to develop the website of the Sumberwringin Bondowoso tourist village as a strategy to expand the market and strengthen local identity. The website is designed to be a digital promotional medium that displays the potential of nature, culture, and creative products of the community in a structured and easily accessible manner. The method used includes three stages, namely planning in August 2025 with the identification of village potential and the preparation of content concepts, implementation from September to October 2025 in the form of website structure construction, content filling, and manager training, and evaluation in October 2025 to assess the effectiveness and response of the community and tourists. The results of the activity show that the website has succeeded in expanding the reach of promotion, increasing public involvement in digital content management, and opening up opportunities for cooperation with external parties. The website also strengthens the image of the village as a cultural and nature-based tourist destination. The discussion emphasized that digitalization through websites is an important factor in the development of sustainable tourism. This is in line with previous research which states that the use of information technology is able to increase the competitiveness of tourist destinations and expand the market. Thus, the development of the Sumberwringin tourism village website makes a real contribution to the growth of the creative economy and the sustainability of the village.